LEVERAGING TECHNOLOGIES TO ENHANCE DIGITAL COMPETENCY IN OFFICE TECHNOLOGY AND MANAGEMENT PROGRAMME IN FEDERAL POLYTECHNICS IN SOUTH-EAST NIGERIA: A CURRICULUM ISSUE (NAU Journal of Technology and Vocational Education, 2026)
This study tried to ascertain the emerging technologies required in Office Technology and Management (OTM) programme in Federal Polytechnics in South-East Nigeria for enhanced digital competency amongst its graduate.  It also sought to find the place of curriculum in effective integration of these technologies into the programme.  Three research questions guided the study and two null hypotheses were tested.  Survey research design was adopted for the study.  The population of the study was 32 OTM lecturers drawn from three Federal polytechnics in South-East offering OTM.  There was no sampling because the size was manageable.  The instrument for data collection was a structured questionnaire on a four-point rating scale.  Data collected were analysed using mean and standard deviation to answer the research questions and ascertain the homogeneity of the responses’ mean. The hypotheses were tested at 0.05 level of significance using t-Test.  The findings of the study showed that modern technologies such as e-learning tools, digital marketing tools, and online communication technologies are some of the emerging technologies required to enhance digital skills competency in OTM and equip the graduates for the modern offices. The study also found that measures like industry collaboration as one of most effectives in ensuring regular review of OTM curriculum with a view to making it reflective of technological trends, adequately prepare its products for the modern office and reduce skills mismatch.  There was no significant difference in the mean ratings of lecturers with over fifteen years of experience and those below on the emerging technologies required for enhanced digital skills acquisition in OTM programme.  The study concluded that modern technologies for enhanced digital skills acquisition are essential in OTM, if the graduates will remain employable in a digital age.  It then recommended that federal polytechnics in South-East should effectively collaborate with feeder industries in the Region for curriculum enrichment and adequate students’ exposure to modern office realities.
Keywords: Digital Skills; Emerging Technologies; Curriculum; OTM Students